Influence of the economic and financial condition of strategic shareholders upon the market value of commercial banks in the Polish banking sector - Zbigniew Korzeb (e-Finanse: Financial Internet Quarterly, 2014)
The objective of the paper is to analyse the influence of information about economic and financial problems of strategic shareholders upon the market value of commercial banks operating in the Polish banking sector. The analysis included fourteen such cases from the years 2007 - 2014. The results clearly indicate that investors consider the foundations of the operation of commercial banks in Poland to be very solid. Problems of strategic shareholders led to only slight depreciation of the banks' securities quoted at the Warsaw Stock Exchange in the period directly after publication of the information. Investors decided that problems of parent companies were unlikely to threaten the stability of banks operating in the Polish banking sector.
Keywords: G21; G34; G15; G14; G28; F36; 330; commercial banks; mergers and acquisitions; cross-border; subprime crisis; bank supervision and regulation